Tänka högt med papper och penna - Bengtsson, Bengt Olle (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
A pad of squared paper, a pencil, an eraser, peace and quiet. These are the tools with which I have done most of my research in theoretical population genetics. But what do I do when I solve my equations describing evolutionary processes? Inspired by among others the French mathematician Cédric Villani, I discuss what happens when I chose to consider my research craft as a special kind of work process. Communication turns out to be surprisingly important in the process – particularly between different parts of my own thinking. The primary aim of my work process seems to be to produce the comforting feeling of certainty. To reach this goal, my slow pencil-driven handwriting is often better than efficient and apparently fail-safe computer programs.